2020
DOI: 10.1111/1365-2435.13511
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to diversity‐driven selection and associated rhizosphere microbial communities

Abstract: Plant diversity loss can alter plant–plant and plant–rhizosphere microbiome interactions. These altered interactions, in turn, may exert diversity‐driven selection pressure to which plants respond with phenotypic changes. Diverse plant communities may favour the survival and fitness of individuals with traits that avoid competition. Conversely, monocultures may accumulate species‐specific pests favouring greater investment in defence traits. Yet, it is unknown how altered plant rhizosphere interactions influen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 74 publications
(125 reference statements)
1
20
0
Order By: Relevance
“…This is likely due to the generalist anti‐fungal qualities of the pyrrolizidine alkaloids produced by J. vulgaris (which have been found to stimulate J. vulgaris ‐specific pathogenic fungi) (Hol & Van Veen, 2002) and also higher concentrations of K in the soils conditioned by J. vulgaris . Taken collectively, our results suggest that intergenerational effects generated by PSFs could play a role in shaping grassland plant communities (Hahl et al, 2020; Zuppinger‐Dingley, Flynn, De Deyn, Petermann, & Schmid, 2016).…”
Section: Discussionsupporting
confidence: 62%
“…This is likely due to the generalist anti‐fungal qualities of the pyrrolizidine alkaloids produced by J. vulgaris (which have been found to stimulate J. vulgaris ‐specific pathogenic fungi) (Hol & Van Veen, 2002) and also higher concentrations of K in the soils conditioned by J. vulgaris . Taken collectively, our results suggest that intergenerational effects generated by PSFs could play a role in shaping grassland plant communities (Hahl et al, 2020; Zuppinger‐Dingley, Flynn, De Deyn, Petermann, & Schmid, 2016).…”
Section: Discussionsupporting
confidence: 62%
“…In contrast to the strong effects of soil legacy on soil microbial communities, effects of plant community history were much weaker. This was unexpected because those same plant community history treatments led to significant plant evolutionary responses, including changes in plant–plant interactions (Zuppinger-Dingley et al, 2014; van Moorsel et al, 2018 and 2020) and even altered plant–soil feedbacks (Hahl et al, 2020; Zuppinger-Dingley et al, 2016). These evolutionary changes in the plant communities may have been too small to become influential on the diversity and composition of soil microbial communities that may need more time to develop or are too subtle to detect.…”
Section: Discussionmentioning
confidence: 99%
“…In one of these experiments, the Jena Experiment in Germany (Weisser et al 2017), it was shown that divergent evolutionary changes of plant species in monocultures vs. mixtures during the first 8 yr contributed to this strengthening of the biodiversity–functioning relationship (Zuppinger‐Dingley et al 2014, van Moorsel et al 2018, 2019). Feedbacks between plants and soil organisms, however, had less explanatory power (van Moorsel et al 2018, Schmid et al 2019, Hahl et al 2020).…”
Section: Introductionmentioning
confidence: 99%